RETRACTED: LncRNA CCAT2 promotes the proliferation and metastasis of colorectal cancer through activation of the ERK and Wnt signaling pathways by regulating GNB2 expression - Jinhai Tian; Xu Cao; Zongying Jiang; Jia Wang; Wan Fan; Shaoting Zhang; Sien Zhao; Jianmin Sun (Cancer Medicine, 2024)
Abstract Background Colorectal cancer (CRC) is a prevalent and lethal tumor, with metastasis being the leading cause of mortality. Previous research has indicated that the long non‐coding RNA (lncRNA) CCAT2 is involved in the regulation of various tumor progression mechanisms. However, the precise role of CCAT2 in CRC proliferation and metastasis remains ambiguous. This study seeks to elucidate the mechanisms through which CCAT2 influences CRC. Methods High‐throughput sequencing and RT‐qPCR were used to detect CCAT2 expression in CRC. Functional analyses including CCK8, colony formation, wound healing migration, transwell chamber, and Muse® Cell Analyzer assays were performed to study the effects of CCAT2 gene deletion on CRC cells. RNA‐pulldown and protein mass spectrometry were employed to identify the interaction between CCAT2 and GNB2 protein. Results Increased CCAT2 expression was found in CRC, especially in metastatic CRC. Deletion of CCAT2 gene inhibited CRC cell proliferation, migration, and invasion while promoting apoptosis. The interaction between CCAT2 and GNB2 protein was shown to modulate GNB2 protein alterations and affect the ERK and Wnt signaling pathways, thereby promoting CRC proliferation and metastasis. Conclusion CCAT2 plays a crucial role in CRC progression by modulating the ERK and Wnt signaling pathways through its interaction with GNB2. These findings highlight the importance of CCAT2 as a key regulatory element in the mechanisms underlying CRC proliferation and metastasis.